Modifikasi Perilaku untuk Memperbaiki Profil Kualitas Diet dan Komposisi Tubuh Remaja Santri yang Kelebihan Berat Badan: Behaviour Modification to Improve Profile of Diet Quality and Body Composition of Overweight and Obesity Islamic Students - Fidiasari, Intan Sepna; Dieny, Fillah Fithra; Nugraheni, Arwinda; Noer, Etika Ratna (Amerta Nutrition, 2024)
Background: The prevalence of overweight and obesity in adolescents is significantly high. Overweight and obesity among Islamic students (referred to as santri in Indonesian) are caused by low diet quality, characterized by inappropriate food intake and low physical activity (energy expenditure). Behavior modification is needed to improve diet quality and body composition. Objectives: This study aimed to analyze the effects of a nutrition class on diet quality, body fat percentage, and waist circumference among female Islamic boarding school students. Methods: This quasi-experimental investigation employed a pre-post test group design with 34 subjects who met the inclusion criteria. The subjects consisted of 17 treatment and 17 control subjects. The treatment group participated in a santri nutrition class involving four nutrition education sessions and 12 aerobic exercise sessions in a month. Diet quality data were gathered using the Diet Quality Index-International (DQI-I) form. Body fat percentage was measured using bioelectrical impedance analysis (BIA), and waist circumference was measured using Medline. Data were analyzed using the independent t-test, Mann-Whitney test, Wilcoxon test, and paired t-test. Results: Subjects with overweight and obesity exhibited low diet quality. Differences in diet quality changes, variation, and adequacy components were observed between the treatment and control groups (p-value=0.001, 0.029, 0.001, respectively). There was no significant differences in changes in body fat percentage and waist circumference between the two groups (p-value=0.487, 0.385, respectively). Conclusions: The santri nutritional class positively impacts diet quality, variation score, adequacy score, and waist circumference among overweight and obese female Islamic boarding school students.